Eficacia de un Programa Educativo en el nivel de conocimientos sobre Hipertensión Arterial en Adultos Mayores. Programa del Adulto Mayor del C.M.I." Santa Lucía"-Moche 2015 - Aguilar Aguilar, Jesús Angel (2016)
This study is quantitative, experimental pre and by the aim pursued Basic, held in the unit of C.M.I Elderly "Santa Lucia" - Moche; during the month of October 2015, it aims to determine the effectiveness of the educational program "Controlling my blood pressure" in the level of knowledge of the Elderly with hypertension (HTA). The sample consisted of 30 older adults with hypertension. The information was obtained through the instruments: Test to assess the level of knowledge of the elderly with hypertension. The results were processed, analyzed and presented in statistical tables and graphs double entry. The results showed that older adults with hypertension studied before implementing the educational program presented regular knowledge level with 56.7 percent to a level of good understanding with 43.3 percent. After application of the educational program in older adults with hypertension presented a good level of knowledge with 100 percent. The educational program was effective to significantly improve the level of knowledge of older adults with hypertension. Keywords: Education Program, level of knowledge, hypertension (